Dynamic analysis of micro-milling machine - Hassan, S.; A. Rahim, E.; Mohid, Z.; Warap, N.M. (Trans Tech Publications, 2014)
Dynamic analysis is very important in developing machine structure to sustain the required accuracy, reliability and productivity. The objective of this study is to conduct a dynamic and modal analyses of micro-milling machine. The machine designs were predicted by comparing the Finite Element Analysis (FEA) using ANSYS software and experimental hammer testing. Two micro-milling machine designs have been proposed. Natural frequency and mode shape was analyzed in modal analysis which show the result that first mode recorded frequency of 92.086 Hz for design A and 154.78 Hz for design B. Natural frequency of design B was higher than design A. From the comparision, it can be concluded that Design B was selected as a best design.